Stabilization of Black Cotton Soil Using Marble Dust Lime and Cement: Enhancing stability of Black cotton soil using marble dust, lime, and cement (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The Black cotton soil is also termed as “Expansive soil”. The B.C. soil properties are mainly influenced by the nature during various seasons like summer season it shrinks and during rainy season it get swells. The objective of The B.C. soils most likely to suitable for the agriculture purpose. In order to use for the construction field it’s important to stabilize the Black cotton soil. There rein this study the black cotton soil properties are studied by using admixtures of marble dust lime concrete AMD cement. In this study the black cotton soil is collected from the bhalki at a depth of 1.5M and the marble dust was gathered from marble cutting industry Gulbarga area. These admixtures such as marble dust, lime, cement and concrete were mixed with clay for further purpose to carry out research. And the study which discussed about During the preceding of the test the B.C.soil properties are studied by various lab test and later admixtures W.C and MDLC are added to the soil in 5,10,15,20, by the weight of the B.C. soil and then soil properties are tested by SPT,UCS, and Direct test are conducted to find the MDD and OMC of a soil, compressive strength and shear parameters of a B.C.soil respectively